Development of Finger Scanner Integrated Absention Web Application in Astra Manufacturing Polytechnic - Ariyanto, Sisia Dika; Fariani, Rida Indah; Goffar, Eko Abdul (Sekolah Tinggi Teknologi Adisutjipto, 2019)
Astra Manufacturing Polytechnic is educational institution under the auspices of PT Astra International (Astra Group) which has total of approximately 700 students. Industrial culture is adopted by applying discipline in the form of attendance. Students who do not arrive on time will be charged Minus Hours. Students do attendance with attendance cards and recapitulated by each study program admin and takes 700 minutes (all study programs) every week to produce minus hours as calculation of student errors. Many students are cheating in the attendance process. Because attendance cards can be deposited to other students. To overcome this, the attendance method was replaced by initially using machine and attendance card with finger scanner and integrated finger scanner integrase application with sql server database. So hopefully cheating and recapitulation time can be eliminated. In the implementation of this research extreme programming is used as software development methodology. After implementation of the application is able to eliminate 700 minutes and eliminate the use of attendance cards.